Analisis Komparatif Produksi Dan Pendapatan Usahatani Bawang Merah Organik Dan Non Organik Di Desa Oloboju Kecamatan Sigi Biromaru Kabupaten Sigi Analysis OfComparative Production and Income FarmOnion Organic and Non-Organic In Oloboju Village Sigi Biromaru Subdistrict, Sigi Regency - Dewi Vebriyanti; Made Antara; Effendy Effendy (Agroland: Jurnal Ilmu-ilmu Pertanian, 2018)
ABSTRACTThe objective of this research was to determine the income of organic and non-organic shallot farming system, to determine the significant difference of production and income of organic and non-organic shallot farming system. This study was conducted from September to October 2017 and its location was purposively determined. Respondents were selected through a Proportional Stratified Random Sampling technique based on the way the respondents practiced the shallot cultivation either organically or non-organically.  The first respondents were 12 farmers and while the others were 18 farmers.  The analysis tool used in this research was the income and comparative analyses. The average income was found to be IDR 12,379,686/ha/planting season (PS) for the organic farming system and IDR 8,031,033/ha/PS for the non-organic farming system. The t-count value was 49.647 at α 5%> t-table 2.048 when the productions of the two farming system were compared and it was 50.975 at α 5% > t-table 2.048 when their incomes were compared. This means H0 is rejected and H1 is accepted which means that the average production and income of the organic shallot farming system is significantly different from those of the non-organic farming system. Keywords : Comparative, income, production, shallot organic and non-organic.